3D numerical modelling of marine organic matter distribution: example of the early Jurassic sequences of the Lusitanian Basin (Portugal). (17th August 2016) - Bruneau, Benjamin; Chauveau, Benoit; Duarte, Luis Vitor; Desaubliaux, Guy; Moretti, Isabelle; Baudin, François
Abstract: Due to the multiple controlling factors involved, it is a challenging task to identify and quantify the processes influencing the distribution and heterogeneity of marine organic‐rich rocks. To improve our understanding of these deposits, we model their burial history and stratigraphic evolution as well as processes linked to marine organic matter history throughout the Lower Jurassic in of the Northern Lusitanian Basin (Western Iberian Margin). This 15‐Ma‐long interval is modelled using 100‐kyr time steps to simulate lithologies and organic matter heterogeneity as layers with a thickness of 2–5 m, depending on the sedimentation rate in the basin. The model is calibrated by well and outcrop data which provide structural and biostratigraphic constraints, as well as information on the depositional facies and geochemistry of the sediments. The results show that the presence of organic‐rich intervals is linked to first‐order variations in the basin geometry and sedimentation rates. Without considering any variation of primary productivity or oxygen content in surface sea waters, the parameters of basin geometry and sedimentation rate are sufficient to predict the main characteristics of source rocks, i.e. their occurrence, thickness and mineralogy at the basin scale. However, to fit the measured organic carbon contents, we need to take account of other parameters such as variations of primary productivity or changes in dissolved oxygen concentration.